Stone selection by wild chimpanzees shares patterns with Oldowan hominins - Braun, D. R. (2025)
The use of broad tool repertoires to increase dietary flexibility through extractive foraging behaviors is shared by humans and their closest living relatives (chimpanzees, Pan troglodytes). However, comparisons between tool use in ancient human ancestors (hominins) and chimpanzees are limited by differences in their toolkits. One feature shared by primate and hominin toolkits is rock selection based on physical properties of the stones and the targets of foraging behaviors. Here, we document the selectivity patterns of stone tools used by wild chimpanzees to crack nuts at Bossou, Guinea, through controlled experiments that introduce rocks unknown to this population. Experiments incorporate specific rock types because previous studies document hominin selection of these lithologies at Kanjera South 2 Ma. We investigate decisions made by chimpanzees when selecting stones that vary in their mechanical propertiesdfeatures not directly visible to the individual. Results indicate that the selection of anvils and hammers is linked to task-specific mechanical properties. Chimpanzees select harder stones for hammers and softer stones for anvils, indicating an understanding of specific properties for distinct functions. Selectivity of rock types suggests that chimpanzees assess the appropriate materials for functions by discriminating these 'invisible' properties. Adults identify mechanical properties through individual learning, and juveniles often reused the tools selected by adults. Selection of specific rock types may be transmitted through the reuse of combinations of rocks. These patterns of stone selection parallel what is documented for Oldowan hominins. The processes identified in this experiment provide insights into the discrete nature of hominin rock selection patterns in Plio-Pleistocene stone artifact production.